(untitled) (Bangladesh Journal of Agriculture, 2023)
A field experiment was conducted in the Agroforestry Field Laboratory of Bangladesh Agricultural University (BAU), Mymensingh, during the period from November 2016 to April 2017 to find out the response of Rain tree (Samanea saman), Ipil-Ipil (Leucaena leucephala), and Minjiri (Senna siamea), leaves biomass with different fertilizers dose applications to yield and yield contributing character of Chinese Hybrid Rice cv. SQR6. Ten treatments were used for the Randomized Complete Block Design (RCBD) with three replications. The results showed that green LB had a significant effect on crop characters viz., plant height, panicle length, no. of tillers hill-1, no. of leaves hill-1, no. of panicles hill-1, no. of effective tillers hill-1, no. of non-effective tillers hill-1, no. of spikelets panicle-1 and 1000-grain weight. The panicle length varied from 22.30 to 25.11 cm. The number of leaves on hill-1 varied from 62.00-26.00. The number of effective tillers on hill-1 varied from 12.23-10.24 whereas the number of non-effective tillers on hill-1 varied from 3.10-1.29. The maximum grain yield of 8.96 t ha-1 was obtained from Treatment T10 followed by T6 where Ipil-Ipil of LB with 45% RFD was applied with a grain yield of 8.63 t ha-1. Therefore, this study suggests that the green LB of Ipil-Ipil and Minjiri could be used the improvement of yield contributing characteristics of rice. Bangladesh J. Agri. 2022, 47(2): 133-142